B - NEARLY COMPACT SPACES - Rao, K. Chandrasekhara (Journal of Global Research in Mathematical Archives(JGRMA), 2014)
Â The main focus of this paper is to introduce the B - nearly compact spaces and study its properties. Keywords: B - nearly compact spaces